2004
DOI: 10.1093/intimm/dxh059
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of DNAM-1 (CD226) interaction with its ligands PVR (CD155) and nectin-2 (PRR-2/CD112)

Abstract: CD226 (DNAM-1) is an adhesion molecule involved in NK and T cell-mediated cytotoxicity against certain tumors. Here, we have identified the human poliovirus receptor-related (PRR) family members CD155 [poliovirus receptor (PVR)] and CD112 (nectin-2/PRR-2) as the ligands for human CD226. Ectopic expression of human CD155 and/or CD112 rendered mouse BW5147 T cells more susceptible to IL-2-activated T and NK cell-mediated cytotoxicity, and killing was specifically inhibited by anti-CD226 mAb, demonstrating functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
213
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(223 citation statements)
references
References 16 publications
7
213
2
1
Order By: Relevance
“…These results are consistent with data from Reymond et al who have shown that DNAM-1 binds Necl-5 more efficiently than Nectin-2 and that Necl-5 but not Nectin-2 is the major ligand of DNAM-1 on endothelial cells [30]. Tahara-Hanaoka et al have suggested that DNAM-1 interactions with Nectin-2 may be impaired by homophilic ligation of Nectin-2 [19]. We had already shown that the NK receptor NKG2D was involved in gd T-cell-mediated lysis of HCC cells expressing the corresponding ligands [5].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with data from Reymond et al who have shown that DNAM-1 binds Necl-5 more efficiently than Nectin-2 and that Necl-5 but not Nectin-2 is the major ligand of DNAM-1 on endothelial cells [30]. Tahara-Hanaoka et al have suggested that DNAM-1 interactions with Nectin-2 may be impaired by homophilic ligation of Nectin-2 [19]. We had already shown that the NK receptor NKG2D was involved in gd T-cell-mediated lysis of HCC cells expressing the corresponding ligands [5].…”
Section: Discussionsupporting
confidence: 92%
“…Our experiments indicate that Necl-5 but not Nectin-2 is involved in the DNAM-1-dependent recognition of tumor cells by gd T cells. Blockade ability of the anti-Nectin-2 mAb (R2.477) was not questioned since this mAb was able to block cytotoxic activity of NK cells against transfectant cells expressing Nectin-2 [19]. These results are consistent with data from Reymond et al who have shown that DNAM-1 binds Necl-5 more efficiently than Nectin-2 and that Necl-5 but not Nectin-2 is the major ligand of DNAM-1 on endothelial cells [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known as a costimulatory and adhesion molecule (33, 34) and mediates activation signals for cytotoxicity by CD8 + T cells and NK cells via its binding to CD155, CD112, or both on target cells (35,36). The important function of CD226 is well known as the immune surveillance of tumors (37).…”
Section: Discussionmentioning
confidence: 99%
“…La molécule DNAM-1 est constitutivement exprimée par les cellules NK humaines [6] et les lymphocytes TV9V2 [24]. Elle interagit avec nectine-2 et Necl-5, et favorise ainsi la fonction cytolytique des cellules NK [25,26] (Figure 3). Pour les lymphocytes TV9V2, des expériences menées sur des lignées d'hépatocar-cinome ont révélé que l'engagement de DNAM-1 avec Necl-5 (mais pas avec nectine-2) participe aussi à leur capacité de reconnaissance et de lyse des cellules tumorales.…”
Section: Rôle Des Nectines/nectines-like Dans Le Développement Tumoralunclassified